Urban rural differentials in spatial distribution of pregnant women’s choice of delivery place by district in Punjab — Results from Pakistan Social and Living Standards Measurements Survey 2014-15 - Masood Ali Shaikh (Journal of the Pakistan Medical Association, 2022)
Madam, home deliveries are fraught with higher risks of maternal and neonatal complications, but in many developing countries childbearing women choose to deliver at home.1-3 Utilization of public or private maternal healthcare services is predicated on availability of, access to, and cost concerns. Public sector healthcare facilities are designed to essentially provide free services.1-3 In this study, percent of delivery sites utilization, disaggregated by urban and rural residency status in each district of the Punjab province were mapped using Geographic information Systems. The spatial distribution of delivery site percentages, disaggregated by three places of either home delivery, delivery at government facilities (hospital, Rural Health Center, and Basic Health Units), and delivery at private hospitals or clinics was done to highlight the urban and rural distribution, including the differences between urban and rural percentages. Continues...